Trauma-informed interventions in probation: a framework for ethical supervision and sustainable desistance - Mihăilă, Maria-Marinela (Technium Social Sciences Journal, 2025)
The integration of trauma-informed care (TIC) principles into probation services marks a critical shift toward more ethical, empathetic, and effective offender supervision. This narrative review examines the role of trauma-informed interventions within probation contexts, highlighting how unaddressed trauma histories can hinder rehabilitation, compliance, and desistance from crime. Drawing on interdisciplinary literature from psychology, criminology, and social work, the paper synthesizes evidence on the prevalence of adverse childhood experiences (ACEs) and complex trauma among justice-involved individuals and explores how these factors intersect with recidivism and behavioral dysregulation. The review maps out key components of trauma-informed probation—including trust-building, safety, collaboration, and individualized care—while evaluating emerging models such as therapeutic jurisprudence, reflective supervision, and integrated service coordination. Challenges related to institutional culture, professional training, and systemic fragmentation are also discussed. The paper concludes by proposing a set of practice recommendations aimed at embedding TIC principles into probation systems through cross-sector collaboration, trauma screening, and survivor-informed supervision strategies. This approach offers the potential not only to reduce reoffending but also to promote psychological resilience and meaningful social reintegration.